The Influence of OTA Marketing Communication on Room Booking Decisions at The Sultan Hotel Jakarta - Murhadi; Nasywa Husnia; Ritasari (Politeknik Sahid, 2026)
This study aims to analyse the influence of Online Travel Agent (OTA) on room booking decisions at The Sultan Hotel & Residence Jakarta. The background of this research departs from the increasing role of OTAs in the hospitality industry as one of the main channels of digital marketing that influences consumer behaviour in the booking process. This study uses a quantitative approach with a survey method on respondents who have booked rooms through OTA. OTA variables are measured through indicators of ease of access, promos or discounts, competitive prices, and customer reviews, which are assumed to influence interest, purchase decisions, and customer satisfaction. The results of simple linear regression analysis showed that OTA had a significant influence on room booking decisions, with a determination coefficient value (R²) of 56.8%. The hypothesis test (t-test) showed significant results (sig. 0.000 < 0.05), which confirmed a strong relationship between OTA use and increased room bookings. These findings highlight the importance of digital marketing communication for hotels in maximizing the potential of OTAs to increase room sales, strengthen competitiveness, and optimize the management of customer information and reviews to improve customer satisfaction. Theoretically, this study contributes to the development of digital marketing communication theory, particularly in explaining how OTA platforms function as persuasive communication media that integrate information quality, promotional attractiveness, and electronic word-of-mouth in shaping consumer decision-making in the hospitality sector